Exogenous gibberellin suppressed taproot secondary thickening by inhibiting the formation and maintenance of vascular cambium in radish (Raphanus sativus L.) - Meng, Ge; Yong, Mingli; Zhang, Ziyue; Zhang, Yuqing; Wang, Yahui; Xiong, Aisheng; Su, Xiaojun (Frontiers in Plant Science, 2024)
The thickening of radish taproots is primarily determined by secondary growth driven by the vascular cambium and is a highly intricate process regulated by plant hormones, transcription factors, and many metabolic pathways. Gibberellin (GA), a plant hormone associated with cell elongation, is essential in secondary growth. However, the mechanism through which exogenous GA3 regulates secondary taproot growth in radishes remains unclear. Integrated morphological, anatomical, hormonal, and transcriptomic analyses of taproots in radishes treated with GA3 and its biosynthesis inhibitor paclobutrazol (PBZ) were performed to explore their effects on taproot secondary growth and key regulatory pathways. GA3 significantly hindered taproot thickening by inhibiting the formation and maintenance of the vascular cambium, and PBZ promoted root development by increasing root length rather than root diameter. Transcriptome analysis revealed 2,014, 948, and 1,831 differentially expressed genes identified from the control CK vs.vs. GA3, controlCK vs.vs. PBZ, and GA3 vs.vs. PBZ comparisons, respectively. Kyoto Encyclopedia of Genes and Genome pathway enrichment analysis revealed that differentially expressed genes were primarily involved in the biosyntheses of secondary metabolites and metabolic pathways. GA3 significantly increased the levels of endogenous indole-acetic acid and the expression of auxin synthesis and signal transduction genes. Exogenous GA3 significantly inhibited the expression of genes involved in the maintenance and differentiation of vascular cambium, including WOX14, ER/ERL1, and XCP2. Exogenous GA3 affects root thickening in radishes primarily by regulating hormone signal transduction pathways, vascular cambium activity, and substance and energy metabolisms. Our findings provide insights into the mechanisms underlying taproot thickening in radishes and provide a valuable gene database for future studies.